2003
DOI: 10.2337/diabetes.52.4.1023
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin Expression Is Reduced in Human Diabetic Nephropathy

Abstract: We studied the distribution of nephrin in renal biopsies from 17 patients with diabetes and nephrotic syndrome (7 type 1 and 10 type 2 diabetes), 6 patients with diabetes and microalbuminuria (1 type 1 and 5 type 2 diabetes), and 10 normal subjects. Nephrin expression was semiquantitatively evaluated by measuring immunofluorescence intensity by digital image analysis. We found an extensive reduction of nephrin staining in both type 1 (67 ؎ 9%; P < 0.001) and type 2 (65 ؎ 10%; P < 0.001) diabetic patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
257
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(287 citation statements)
references
References 46 publications
26
257
0
4
Order By: Relevance
“…Nephrin has also been associated with diabetic nephropathy, with reduced nephrin levels in human biopsies from patients with diabetes and proteinuria [12]. It has been proposed that this contributes to the development of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nephrin has also been associated with diabetic nephropathy, with reduced nephrin levels in human biopsies from patients with diabetes and proteinuria [12]. It has been proposed that this contributes to the development of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…An early marker of this state is microalbuminuria. There is now good evidence that glomerular podocytes are directly targeted in diabetic nephropathy with loss of podocytes into the urine [11] and reduced production of the key podocyte protein nephrin [12]. These phenomena may be mechanisms that lead to disruption of the glomerular filtration barrier and to disease progression in diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…In cultured mesangial cells, Ang II [35][36][37] and aldosterone 38,39 provoke synthesis of extracellular matrix (ECM) proteins that accumulate in glomerulosclerosis. In podocytes, Ang II has been shown to induce apoptosis, 40,41 cytoskeletal rearrangement 42 and nephrin loss 43 in podocytes, alterations that have been linked to albuminuria. 44 Aldosterone can also damage podocytes by inducing apoptosis and reducing nephrin gene expression.…”
Section: Intrarenal Raasmentioning
confidence: 99%
“…Glomerular nephrin mRNA was decreased in biopsies of type 2 diabetic patients who had proteinuria, while the results were similar to those in control subjects when the ACE inhibitor perindopril was used [26]. Another study demonstrated a similar reduction in nephrin protein with altered cellular distribution in biopsies of type 1 and type 2 diabetic patients with the nephrotic syndrome [27]. A particularly interesting finding in that study was that angiotensin II caused the excretion of a 100-kDa protein from the glomerular epithelial cells [27].…”
Section: Discussionmentioning
confidence: 62%
“…Another study demonstrated a similar reduction in nephrin protein with altered cellular distribution in biopsies of type 1 and type 2 diabetic patients with the nephrotic syndrome [27]. A particularly interesting finding in that study was that angiotensin II caused the excretion of a 100-kDa protein from the glomerular epithelial cells [27]. This protein was detectable with an anti-nephrin antibody, and the excretion phenomenon may have involved cytoskeletal rearrangement.…”
Section: Discussionmentioning
confidence: 71%